Effects of Moderation Training on Financial Report Preparation, HR Quality, SAK EMKM Implementation and Financial Reporting - Has, Fandri Riomanugusta; Kamaliah, Kamaliah; Azlina, Nur (The International Journal of Business Review (The Jobs Review), 2020)
This study aims to examine the effect of the quality of human resources and the implementation of SAK EMKM on MSME financial reporting by training in preparing financial statements as a moderating variable. The population in this study were all MSMEs in Bengkalis Regency and the sample in this study amounted to 110 MSMEs. The sampling method uses incidental sampling. Data analysis methods used in this study are multiple regression analysis and MRA using SPSS version 25.0. The results of this study indicate that the quality of human resources and the implementation of SAK EMKM affect the financial reporting of MSMEs. Then the training on the preparation of financial statements moderates the relationship between the quality of human resources and the implementation of SAK EMKM towards MSME financial reporting